Molecular analysis of a novel DNA transposon in Triticeae - Thiyagarajan K.; Cantale C.; Galeffi P. (Proceedings of the International Symposium on Genetics and breeding of durum wheat, 2014)
A novel non-autonomous transposon element was identified in durum wheat and in various Aegilops speltoides accessions from the Fertile Crescent. It shows the standard transposon signals, such as a terminal inverted repeat (TIR-18bp), target site duplications (TSD-2bp-TC), many internal inverted repeats and a variable number of tandem repeats and does not code for a transposase enzyme. Interestingly, it is located inside the Dehydration Responsive Factor 1 (TdDRF1) gene which codifies for transcription factors involved in the early response to drought by an alternative splicing mechanism. The transposon encompasses the gene sequence, from intron 1 to intron 3, including two translated regions, the exon 2 and the exon 3. Due to its peculiar position inside the CDS, a possible involvement in the molecular evolution of the gene was hypothesized. The transposon sequence and signals in all available relevant sequences from the same tribe, such as Triticum durum, T. urartu, A. tauschii were analysed and compared with the aim of drawing its phylogenetic story.
International Symposium : Genetics and Breeding of Durum Wheat, 2013/05/27-30, Rome (Italy)